The arrival - Tan, Shaun (New York, NY : A.A. Levine, 2007)
In this wordless graphic novel, a man leaves his homeland and sets off for a new country, where he must build a new life for himself and his family.
Added t.p. in unknown script.
A Junior Library Guild selection
Keywords: Emigration and immigration -- Comic books, strips, etc. -- Juvenile literature; Immigrants -- Comic books, strips, etc. -- Juvenile literature; Stories without words -- Juvenile literature; Comic books, strips, etc; Graphic novels